The apothecary - Meloy, Maile; Schoenherr, Ian (New York : Puffin Books, 2013)
Fourteen-year-old Janie Scott, newly arrived in London from Los Angeles in 1952, becomes friends with a mysterious apothecary and his son, Benjamin Burrows, and is drawn into a dangerous adventure with Benjamin when his father is kidnapped and Russian spies try to steal his book of secrets.
Wilson's Junior High School, October 2012
School Library Journal, December 2011
Pub Weekly, September 2011
New York Times, October 2011
Horn Book, April 2012
Bulletin (Center for Children's books), November 2011
Keywords: Cold War -- Juvenile fiction; Alchemy -- Juvenile fiction; London (England) -- History -- 20th century -- Juvenile fiction; Great Britain -- History -- Elizabeth II, 1952- -- Juvenile fiction; Cold War -- Fiction; Alchemy -- Fiction; London (England) -- History -- Fiction; Great Britain -- History -- Elizabeth II, 1952- -- Fiction; Adventure and adventurers -- Fiction; Cold war -- Fiction; Alchemy -- Fiction; London (England) -- History -- Fiction; Great Britain -- History -- 1952- -- Fiction; Adventure fiction; Adventure fiction